2004
DOI: 10.4141/s03-084
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus diffusion from monocalcium phosphate co-applied with salts in a calcareous soil

Abstract: . 2004. Phosphorus diffusion from monocalcium phosphate coapplied with salts in a calcareous soil. Can. J. Soil Sci. 84: 447-458. Mixing non-phosphatic salts with fertilizer P influences the solubility and mobility of P in soils. Little evidence, however, is available regarding the mechanisms causing such effects. The objectives of this study were to investigate the effects of mixing fertilizer P with (NH 4 ) 2 SO 4 , MgSO 4 or (NH 2 ) 2 CO on the diffusion of P in a calcareous soil (Gleyed Rego Black Chernoze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Hammond (1997) reported that, of all the salts evaluated, ammonium sulphate was the most effective at increasing the crop utilization of P when banded with monoammonium phosphate fertilizer. Kumaragamage et al (2004) also found that the solubility of P was increased by more than twofold when monocalcium phosphate fertilizer was mixed with ammonium sulphate or magnesium sulphate, and by 1.2-fold when mixed with urea. The difference between the effect of sulphate salts and urea on P solubility was attributed to the competition between SO 4 2( and HPO 4 2( for precipitation reaction with Ca 2' .…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…Hammond (1997) reported that, of all the salts evaluated, ammonium sulphate was the most effective at increasing the crop utilization of P when banded with monoammonium phosphate fertilizer. Kumaragamage et al (2004) also found that the solubility of P was increased by more than twofold when monocalcium phosphate fertilizer was mixed with ammonium sulphate or magnesium sulphate, and by 1.2-fold when mixed with urea. The difference between the effect of sulphate salts and urea on P solubility was attributed to the competition between SO 4 2( and HPO 4 2( for precipitation reaction with Ca 2' .…”
mentioning
confidence: 87%
“…The enhanced solubility and diffusion of P in the K 2 SO 4 column was probably due to both pH reduction and competition of SO 4 2( against HPO 4 2( for precipitation with Ca 2' (Kumaragamage et al 2004;Olatuyi 2006). There was no marked differences in P solubility between KH 2 PO 4 alone and KH 2 PO 4 'KNO 3 treatment, but KNO 3 had greater P solubility than K 2 CO 3 or KCl.…”
Section: Extractable Phosphorus In the Potassium Systemmentioning
confidence: 97%
See 3 more Smart Citations